Diaspore traits specialized to animal adhesion and sea current dispersal are positively associated with the naturalization of European plants across the world - Moyano, Jaime (2022)
Understanding what drives non-native species naturalization (the establishment of a self-sustainable population outside its native range) is a central question in invasion science. Plant capacity for long-distance dispersal (LDD) is likely to influence the spread and naturalization of non-native species differently according to their introduction pathways. These pathways include intentional introductions (for economic use, e.g. for agriculture), unintentional introductions (e.g. seed contaminants), plant dispersal via human infrastructures (e.g. roads) and plant spread from an adjacent region where the species was previously introduced. We tested the relationship between sets of LDD traits (syndromes) of 10 308 European plant species and their global naturalization incidence (i.e. whether a species has become naturalized or not) and extent (i.e. the number of regions where a species has become naturalized) using the most comprehensive database of naturalized plants worldwide (GloNAF). Diaspore traits allowed the identification of four traditional LDD syndromes, namely those with specializations for dispersal by: wind (anemochorous), animal ingestion (endozoochorous), attached to animals (epizoochorous) and sea currents (thalassochorous). These evolutionary specializations have been historically interpreted by biologists even though actual dispersal is not always related to diaspore syndromes. We found that while epizoochorous and thalassochorous traits are positively associated with global plant naturalization incidence, anemochorous and endozoochorous traits show a negative relationship. Species' residence time outside their native range, their economic use and presence of epizoochorous traits (such as hooks, hairs and adhesive substances) are positively associated with global naturalization extent. Furthermore, we found that plant economic use reduces the influence of LDD syndromes on the naturalization incidence of intentionally introduced plants. While the success of non-native plants is influenced by a broad array of species- and context-specific factors, LDD syndromes play an important role in this context depending on the economic use of plants.